The Romano-British 'Aedicule' from Sheepwash Grange, Canwick, Lincolnshire. (November 2020) - Everson, Paul; Stocker, David
ABSTRACT: A stone fragment from recent excavations at Sheepwash Grange near Lincoln is illustrated and discussed. Initially thought to be an early medieval, Christian grave-marker, because of its excavated context, its original form is reconstructed as a carved stone aedicule of Roman date and interpreted as a lararium . The building depicted is timber framed. Analogies from Britain prove at best partial, but contemporary objects of similar form in the Rhineland and Saarland regions provide close parallels and invite discussion of the connection this evidences. While the excavations included a villa complex likely to be the aedicule's immediate context, the location is an ancient river crossing distinctively marked by repeated activity from earliest prehistory.